Pendekatan Holistik dalam Perencanaan Pendidikan Islam: Strategi dan Implementasi di Era Modern - Romdomiyah, Fida Fadilatul (Epistemic: Jurnal Ilmiah Pendidikan, 2023)
Educational planning is a crucial element in achieving desired educational goals at both national and local levels. This study aims to explore the planning process in Islamic education. The methodology used is a literature review, examining various sources such as journals, books, and previous research. This qualitative research design focuses on the analysis and clarification of data obtained from relevant articles and e-books. The key findings indicate that rapid curriculum changes, difficulties in applying knowledge to daily life, and inadequate infrastructure and educational support facilities are significant obstacles in Islamic educational planning. This research provides important contributions to the literature on educational planning, particularly in the context of Islamic education. The study's limitations lie in its literature-based scope, lacking field observations. Future research is expected to address these limitations with empirical studies and deeper analyses. The implications of this study highlight the importance of continuous evaluation and improvement in educational planning to ensure its relevance and effectiveness in facing future challenges.